A Multimodal Architecture with Visual-Level Framework for Virtual Assistant - Varshan V., Shree; Rajakumaran, Gayathri; Usharani, Shola; Vincent, Rajiv (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Virtual personal assistants (VPAs) have grown in popularity due to their scalability and accessibility. The development of machine learning (ML) and natural language processing (NLP) have changed how we use technology and the growth of digital assistant technology. VPAs uses artificial intelligence to personalize, simplify, and automate user tasks and use computer vision to recognize visual cues. Consequently, increasing their versatility and functionality across other inputs. The proposed architecture for the VPA is based on two main components that will work in tandem: a chat-like model that can accept text or speech input to help the user and a computer vision framework that consists of multiple levels to enable control and interaction with the computer using visual input. The VPA utilizes NLP and ML algorithms to read and interpret user queries in both audio and text formats. Based on the classification and context of the query, automated actions are taken by the VPA to improve operational efficiency. The innovative computer vision framework lets the user to control the computer without a mouse or keyboard via gestures and level to represent action in the environment. Eventually, improving user experience by adding convenience and effectiveness. Automated tasks include opening particular apps, creating weather reports based on the location, altering screen brightness and system volume, virtual mouse operation, and manage launched applications such as minimize, maximize, or audio-input with hand gestures. Thus, VPAs save time, boost productivity, and enhance use of technology at home and in the workplace.